Conditioned generalization of social anxiety effects based on positive and negative social evaluations - Huoyin Zhang; Qi Wu; Yukun Huang; Yujing Liu; Jingyuan Lin; Yi Lei (Scientific Reports, 2025)
Abstract While negative social evaluations have been identified as a critical factor in social anxiety, the relationship between social anxiety (SA) levels and the generalization of positive and negative social evaluations remains unclear. To understand this relationship, 2 experiments were conducted. In Experiment 1, a total of 45 participants completed a laboratory-based conditioning and generalization task with neutral faces paired with positive or negative social evaluations. Using morphed versions of these faces as generalization stimuli, participants rated their expectancy of receiving social evaluations for each face. In Experiment 2, high SA and low SA groups (27 in each group) extended these findings by examining whether social anxiety levels modulated the generalization of social evaluations, with the addition of negative emotion ratings as a dependent measure. In Experiment 1, participants’ strong generalization of negative evaluations for stimuli similar to conditioned faces positively correlated with their SA levels. Experiment 2 also demonstrated a positive relation between SA and the generalization of negative evaluations for conditioned faces. Specifically, both high and low SA groups showed generalization in the form of gradual decreases in expectancy ratings as faces became less similar to the conditioned stimuli. However, the high SA group, compared to the low SA group, displayed enhanced negative emotional responses to faces paired with negative evaluations and their morphed variants, with this effect being strongest for faces most similar to the negative-paired faces (i.e., generalization). These results supported the cognitive processing model of social anxiety and highlight the importance of considering evaluation generalization in understanding and treating social anxiety.